Use of Climate Change Projections for Resilience Planning in Rio de Janeiro, Brazil - Barata, Martha M. L.; Bader, Daniel A.; Dereczynski, Claudine; Regoto, Pedro; Rosenzweig, Cynthia (Frontiers in Sustainable Cities, 2020)
In this study we use three different methodologies, document and compare temperature and precipitation projections for the city of Rio de Janeiro (RJ) over the 21st century. It aims to access in what way the differences and similarities of those methodologies and their outcomes, support the incorporation of climate risks in urban planning and improve effective urban climate change governance. We compared the projections for RJ from the Eta Regional Climate Model from the Brazilian National Institute for Space Research nested in two Hadley Center Global Climate Models (GCMs) (Eta-HadCM3 method and Eta-HadGEM2-ES method) and 33 GCMs simulations from the Coupled Model Intercomparing Project Phase 5 multi-model dataset (Urban Climate Change Research Network - UCCRN method). The three methods showed increasing temperatures for RJ in the end of the century. Precipitation projections span from a 13% decrease to a 12 % increase, when using UCCRN method or reduce between 0.4% and 0.5%, when using Eta-HadGEM2-ES method. However, the middle range of the projections from UCCRN and the Eta-HadGEM2-ES projections are similar. The three methods project an increase of warm days and nights and a decrease of cold days and nights. Nevertheless, although the directions of change are the same applying the three methods, the magnitude differs when considering warm and cold nights. Hence, city stakeholders are better informed when we apply different methods as it gives them the opportunity to consider the level of risk, they are willing to bear in the future. We observed that defining climate change projections on the city scale based on clear communication and an interactive process between scientists and stakeholders can be used to inform citywide adaptation strategies and sector-specific uses, as well as, promote urban climate risk governance.